Primary Duodenal Adenocarcinoma Revealed by Chronic Iron Deficiency Anemia: Diagnostic Difficulties in a Case Report in Internal Medicine CNHU-HKM Cotonou - AZON KOUANOU, ANGÈLE; ZANNOU, DJIMON MARCEL; KPOSSOU, ABOUDOU RAÏMI; AGBODANDE, KOUESSI ANTHELME; PRUDENCIO, RDTK; SEHONOU, JEAN; GBESSI, GASPARD DANSOU; GNANGNON, FREDDY HOUEHANOU RODRIGUE; ADE, GABRIEL; HOUNGBE, FABIEN (My University, 2015)
The location of a primary duodenal adenocarcinoma is exceptional. Only few cases have been reported in the literature. We hereby report a case of primary adenocarcinoma of the duodenum with a 60 years old patient admitted because of chronic iron deficiency anemia. Endoscopic examination revealed a budding and ulcerated process in the second duodenum. The biopsy analysis showed primary adenocarcinoma. No other primary tumor was found. The staging directed showed cephalic pancreatic invasion. The patient died in the aftermath of a surgical management.
Keywords: Chronic Iron Deficit; Adenocarcinoma; Duodenum; Benin